The Influence of Learning Difficulties, Teacher's Teaching Creativity, Parents' Education Level and Occupation on the Learning Outcomes of 10th Grade Students in Economics Through Learning Motivation as an Intervening Variable - Icha Agustryani; Jimi Ronald; Ansofino (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the effect of learning difficulties, teachers’ teaching creativity, parents’ educational level, and parents’ occupation on students’ learning outcomes through learning motivation as an intervening variable. This research employed a quantitative approach with a population consisting of all tenth-grade students of SMA Negeri 1 Sipora Selatan in the 2024/2025 academic year, totaling 95 students. The sampling technique used was proportional random sampling. The research instrument was a closed-ended questionnaire, and the data were analyzed using path analysis as well as hypothesis testing through t-test and F-test. The results indicate that learning difficulties, teachers’ teaching creativity, parents’ educational level, and parents’ occupation have a significant effect on students’ learning outcomes, both directly and indirectly through learning motivation. Learning motivation was proven to have a significant effect on students’ learning outcomes. These findings suggest that improving students’ learning outcomes can be achieved by reducing learning difficulties, enhancing teachers’ teaching creativity, and strengthening family support through parents’ education and occupation.